2020
DOI: 10.1002/nop2.741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the effectiveness of breast cancer decision aids: A systematic review and meta‐analysis of randomize clinical trails

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
12
2
1
Order By: Relevance
“…Unlike previous reports (Gao et al, 2021; Schapira et al, 2022; Steenbeek et al, 2021), our results showed no intervention effect on decision self-efficacy. Both groups in our study showed similar improvement from pretest to post-test.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous reports (Gao et al, 2021; Schapira et al, 2022; Steenbeek et al, 2021), our results showed no intervention effect on decision self-efficacy. Both groups in our study showed similar improvement from pretest to post-test.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent literature, decision regret has been described as a negative emotion in response to a poor or unexpected treatment outcome, leading to psychological distress. Women often question whether they made the correct treatment decision 7–9,11,20–22 . Connolly and Reb 23 proposed three types of regret utilizing the decision justification theory used to examine decision regret in recent studies 24,25 …”
Section: Resultsmentioning
confidence: 99%
“…Decision regret is an undesirable experience that most women, if they could, would avoid due to the emotional toll it can inflict 7–9,20–22,24–26,33,34 . A diverse spectrum of negative emotions can be seen in women experiencing decision regret, such as distress, 7,9,30,33,35 guilt, remorse, self‐blame, or recrimination 7,8,21,30,33–35 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, decision making may be in uenced by the views of family members, thereby limiting the participation of patients in this process. It is suggested that medical staff should fully evaluate the decision-making expectations and preferences of patients with breast cancer receiving chemotherapy (particularly those with low self-management e cacy level), actively mobilize relatives of patients with breast cancer, empower patients to actively participate in disease management and treatment decisions, and develop localized and intelligent decision-making aids for patients with breast cancer in China [27]. These measures would improve the treatment decision-making process.…”
Section: E Cacy Of Patients With Breast Cancer Chemotherapy Is At The...mentioning
confidence: 99%